Implementation of the Program Kampus Mengajar (Teaching Campus Program) by Family Welfare Education and Fashion Design Education Students - Wahyuni, Sri; Na’am, Muh Fakhrihun; Wahyuningsih, Sri Endah (Universitas Negeri Semarang, 2023)
The Program Kampus Mengajar (Teaching Campus Program) aims to provide opportunities for students, at least in their fifth semester, to learn and develop outside their study program. Students participating in the Program Kampus Mengajar are guided by Field Supervisor Lecturers who are randomly grouped based on their domicile. The objectives of this study are to analyze the actual conditions of the teaching campus practice in target schools, to analyze the process of mentoring and guidance in teaching campus activities at target schools, to analyze the recognition of credits and course grade conventions, and to analyze efforts to optimize the program. The method used is qualitative, with data collection techniques including observation, interviews, and documentation. The validity of the data is ensured using source triangulation. Data analysis techniques follow the Miles and Huberman model, consisting of three activities: data reduction, data display, and conclusion drawing/verification. The results of the study are: (1) The implementation of the Program Kampus Mengajar has been running well, although there are some obstacles; (2) Mentoring and guidance by supervising teachers and Field Supervisor Lecturers are conducted flexibly; (3) The process of recognizing and converting course grades is in accordance with the curriculum, although some lecturers initially disagreed with their courses being recognized; (4) Efforts to optimize the program are essential for the revitalization and success of the next batch of the Program Kampus Mengajar.